Palestinian Banks Analysis Using CAMEL Model - Zedan, Khaled A.; Daas, Gassan (International Journal of Economics and Financial Issues, 2017)
This study attempts to evaluate the performance and financial soundness of Palestinian commercial banks for the year 2015 using CAMEL rating model. The CAMEL model provides a means to categorized bank based on the overall health, financial status, and managerial operation. Banks were sustained rating based on the performance in five areas: capital adequacy, asset quality, management efficiency, earning quality, and liquidity. We applied capital adequacy ratio (CAR) to analyze capital adequacy parameter, non performing loans to total loans (NPL) to analyze of assets quality parameter, non expense ratio (NER) for analyzing management quality parameter, return on assets (ROA) and return on equity (ROE) to analyze earnings ability and total loans to total deposits ratio (LDR) to analyze liquidity management Keywords: CAMEL approach; financial institutions; Palestine JEL Classifications: G20; G21